Multi-risk Approach to the Qra of Natech Scenarios in the Chemical and Process Industry - Riccardo Sorichetti; Alessio Misuri; Annamaria Di Padova; Roberta Miglionico; Fabrizio Tallone; Valerio Cozzani (Chemical Engineering Transactions, 2022)
A novel quantitative methodology to perform a multi-risk assessment of technological scenarios triggered by natural hazards (Natech events) is presented. The framework is based on a multi-hazard approach and is proposed to assess the risk associated to the different natural events to which an industrial site where relevant quantities of hazardous substances are present is exposed to. The quantitative methodology allows the calculation of failure frequencies, consequences of the scenarios and risk indexes which are compared and benchmarked. Finally, a case study is defined taking into account the impact of earthquakes, floods and lightning strikes. The application leads to the quantification of the contribution of each reference natural event considered to the overall risk figures. Moreover, the methodology proposed enables the evaluation of the relative weight of the risk related to each natural hazard for the selected facility.